Primary Emissions and Secondary Aerosol Processing During Wintertime in Rural Area of North China Plain. Issue 7 (7th April 2022) - Chen, Chun; Qiu, Yanmei; Xu, Weiqi; He, Yao; Li, Zhijie; Sun, Jiaxing; Ma, Nan; Xu, Wanyun; Pan, Xiaole; Fu, Pingqing; Wang, Zifa; Sun, Yele
Abstract: The vast rural areas often experience more severe haze pollution than megacities during wintertime in North China Plain (NCP), yet the sources and evolution processes of aerosol particles, particularly organic aerosol (OA) remain poorly understood. Here we conducted real‐time measurements of submicron aerosol (PM1 ) species using a high‐resolution aerosol mass spectrometer at a representative rural site in NCP in winter 2019. Our results showed the dominance of organics (36%) and nitrate in PM1 (22%) in 2019. Positive matrix factorization analysis illustrated similarly important primary sources from traffic emissions, coal combustion, and biomass burning, yet secondary OA (SOA) from photochemical and aqueous‐phase related processing exceeded primary OA (53% vs. 47%). Substantial decreases in primary species and considerable increases in nitrate and sulphate were observed since winter 2018, demonstrating enhanced secondary formation in winter 2019. OA composition changed significantly from clean period to fog events with the contribution of aqueous phase‐related oxygenated OA increasing from 6% to 44%, while the photochemical SOA decreased correspondingly from 51% to 19%. The size distributions of aerosol species also changed by shifting toward large sizes during fog events. Elemental analysis of OA and the Van Krevelen diagram (H/C vs. O/C) illustrated the different roles of photochemical and aqueous‐phase processing during daytime and nighttime, respectively, and aqueous‐phase processing is subject to the formation of organic compounds with high H/C and O/C ratios. The large differences in fog processing of submicron aerosol species between 2018 and 2019 due to different temperatures were also elucidated. Plain Language Summary: Air quality in megacities in North China Plain (NCP) has been improved significantly during the last decade, however, severe haze pollution events occur frequently in vast rural areas during wintertime. Recent studies have demonstrated stronger health impacts of aerosol particles in rural area than megacities, yet the composition, sources and evolution processes of aerosol particles, particularly organic aerosol (OA) in rural area in NCP remain poorly characterized. Here we have a comprehensive characterization of submicron aerosol species at a rural site in winter in NCP. We observed substantial decreases in primary species and considerable increases in nitrate and sulphate from 2018 to 2019 due to enhanced secondary formation and the decreases in primary emissions. We found similarly important primary sources from traffic emissions, coal combustion, and biomass burning in rural area. However, secondary OA (SOA) from photochemical and aqueous‐phase related processing exceeded primary OA. The aqueous‐phase related SOA increased significantly by up to 44% during fog events, while the photochemical SOA decreased correspondingly from 51% to 19%. The size distributions, elemental composition of OA, and Van Krevelen diagram further illustrated the different roles of photochemical and aqueous‐phase processing in secondary aerosol formation in rural area in NCP. Key Points: Primary organic aerosol (OA) was primarily from coal combustion, biomass burning and traffic emissions in rural North China Plain in winter Aqueous phase‐related OA showed large increases during fog events, while photochemical secondary OA was important during non‐fog periods Aerosol composition showed significant changes from 2018 to 2019 due to enhanced secondary formation and changes in primary emissions